Peningkatan Kemampuan Menyimak Cerita Fiksi Melalui Media Audio Visual Terhadap Hasil Belajar Siswa Kelas III SD Negeri 213 Palembang - Indah Rohmalinda; Dessy Wardiah; Muhammad Ali (Departement of Mathematics Education, 2023)
This study aims to improve the ability to listen to fictional stories through audio-visual media in class III SD Negeri 213 Palembang, improve learning outcomes in learning Indonesian and increase student activity in learning to listen to fictional stories through audio-visual media. The subjects of this study were 17 students in grade III SD Negeri 213 Palembang, consisting of 10 male students and 7 female students. The method used is descriptive quantitative and descriptive qualitative methods. Data collection techniques used are observation and test techniques. This research was conducted in two cycles. Each cycle includes the stages of planning, implementing, observing (observation), and reflecting. Based on the results of the study it can be concluded that learning by using audio-visual media can improve the skills of listening to fiction stories in students. The average result of listening to fictional stories in cycle II was 78.38, an increase of 15.74 from the results of the cycle, which was 62.64. The number of students who met the KKM also increased, in cycle I of 41.18% of students who met the KKM. In cycle II it increased to 94.12% of students who met the KKM. From these data it shows that there is an increase in class III student learning outcomes at SD Negeri 213 Palembang after using audio-visual media in listening to fictional stories.